2021
DOI: 10.1186/s13071-021-04693-7
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-like cell death upon kinetoplastid induction by compounds isolated from the brown algae Dictyota spiralis

Abstract: Background The in vitro activity of the brown seaweed Dictyota spiralis against both Leishmania amazonensis and Trypanosoma cruzi was evaluated in a previous study. Processing by bio-guided fractionation resulted in the isolation of three active compounds, classified as diterpenes. In the present study, we performed several assays to detect clinical features associated to cell death in L. amazonensis and T. cruzi with the aim to elucidate the mechanism of action of these compounds on parasitic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…In vitro evaluation of the trypanocidal activity exhibited IC 50 values ranging from 13.11 to 35.28 µM for these compounds; in comparison to benznidazole, which was active with an IC 50 of 6.95 µM. Regarding cytotoxicity, CC 50 values were found to range from 36.96 µM for pachydictyol C (111) to 69.98 µM for 3,4-epoxy-7,18-dolabelladiene compared to miltefosine and benznidazole [126]. Diterpenes such as dictyol C (24), (8R,11R)-8,11-diacetoxypachydictyol A, (8R*,11R*)-6-O-acetyl-8-acetoxy-11-hydroxypachydictyol A, (8R*,11S*)-8-acetoxy-11hydroxypachydictyol A, and (8R*,11S*)-6-O-acetyl-8,11-dihydroxypachydictyol A, and a secohydroazulene derivative, named 7Z-7,8-seco-7,11-didehydro-8-acetoxypachydictyol A, were detected in Dictyota sp.…”
Section: Dictyota Spiralis Montagne 1846mentioning
confidence: 95%
See 1 more Smart Citation
“…In vitro evaluation of the trypanocidal activity exhibited IC 50 values ranging from 13.11 to 35.28 µM for these compounds; in comparison to benznidazole, which was active with an IC 50 of 6.95 µM. Regarding cytotoxicity, CC 50 values were found to range from 36.96 µM for pachydictyol C (111) to 69.98 µM for 3,4-epoxy-7,18-dolabelladiene compared to miltefosine and benznidazole [126]. Diterpenes such as dictyol C (24), (8R,11R)-8,11-diacetoxypachydictyol A, (8R*,11R*)-6-O-acetyl-8-acetoxy-11-hydroxypachydictyol A, (8R*,11S*)-8-acetoxy-11hydroxypachydictyol A, and (8R*,11S*)-6-O-acetyl-8,11-dihydroxypachydictyol A, and a secohydroazulene derivative, named 7Z-7,8-seco-7,11-didehydro-8-acetoxypachydictyol A, were detected in Dictyota sp.…”
Section: Dictyota Spiralis Montagne 1846mentioning
confidence: 95%
“…Dictyol B acetate (18) and dictyotadiol (118) (Figure 5) are diterpenes from D. dichotoma [62]. Sterols such as methyl-22-dehydrocholesterol, fucosterol (114), coprostanol (119), epicoprostanol (120), campesterol (121), stigmasterol (122), β-sitosterol (123), cholesterol (124), brassicasterol (125), cholestanol (126), and 5β-cholestan-3-one (127) (Figure 6) were discovered in the Malaysian D. dichotoma and tested for antifouling activity against Vibrio alginolyticus, V. mimicus, V. parahaemolyticus, P. aeruginosa, and B. subtilis. Coprostanol (119), epicoprostanol (120), campesterol (121), stigmasterol (122), and 5β-cholestan-3-one (127) (Figure 6) showed strong inhibition towards the selected bacterial strains, with IC 50 values ranging from 266.3 to 425.8 µg/mL, while fucosterol (114) gave no activity for all bacterial strains tested.…”
Section: Dictyota Crenulata J Agardh 1847mentioning
confidence: 99%
“…The graph represented in the Figs. [14][15][16] show the mean values of green fluorescence intensity produced by trophozoites of Acanthamoeba spp. Data indicated that the differences between the mean values of treated cells with compounds 1, 3 and 4, and negative controls cells were significant in all tested strains of Acanthamoeba; * p < 0.05, ** p < 0.01, *** p < 0.001 and **** p < 0.0001.…”
Section: Evaluation Of the Plasma Membrane Damage In Acanthamoeba Sppmentioning
confidence: 99%
“…Among these organisms, macroalgae contains a wide variety of bioactive secondary metabolites including phlorotannins, glycerols, quinones, polyketides, polysaccharide, diterpenoids, phenolic compounds, sterols, cyclic peptide, lipids, and alkaloids [13,14]. Lately, several reports have confirmed the diverse pharmacological properties of seaweeds as antimicrobial, anti-helminthic, cytotoxic, anti-inflammatory, and antiprotozoal among other biological activities [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Propidium iodide (PI) quantitatively stains DNA (S2A,B Fig), but requires cell fixation, and is thus unsuitable for use in live cells. Hoechst 33342 is commonly used to stain the nucleus and kinetoplast in live Leishmania (4042), but IFC indicated that it does not bind proportionally to DNA (S2C Fig). Images of Hoechst-stained cells revealed staining outside of the nucleus that may account for it being non-quantitative (S2C Fig).…”
Section: Resultsmentioning
confidence: 99%